Academic Ethics in the Flow of Digitalization: Maintaining Scientific Integrity in the Age of Technology - Muhammad Zaid Tsabit; Rahmad Ananda; Nayla Desinta Arnain (ISNU Nine-Star Multidisciplinary Journal, 2025)
A person's manners in the current era are influenced by digital influences. The digital era has brought significant changes in the academic world. Including in terms of research ethics. Plagiarism and violations of research integrity are becoming increasingly challenging. This research aims to critically analyze the challenges of academic ethics in the digital age and provide recommendations to improve research integrity. The purpose of this research is to find out the picture of ethics by an academic in the current era. The research methods used are literature analysis and case studies. The results of the study show that awareness of academic ethics needs to be improved, especially in the use of digital technology. This research is expected to contribute to the understanding of academic ethics in the digital age and raise awareness of the importance of research integrity. An academic must implement improvements in digital technology as well as increased awareness of the importance of research integrity